A 50THz Ultra-Wideband Nano-Photonics Perfect Absorber Biosensor for Label-Free Detection of Circulating Cancer Exosomes: Advancing Early Cancer Diagnostics - Musa N. Hamza; Mohammad Tariqul Islam; Sunil Lavadiya; Iftikhar ud Din; Bruno Sanches; Slawomir Koziel; Syeda Iffat Naqvi; Abinash Panda; Mohammad Alibakhshikenari; Bal Virdee; D. Mariyanayagam; R. Jayanthi; et al. (IEEE Photonics Journal)
This paper addresses the challenge of early-stage cancer diagnosis using microwave imaging (MWI) techniques by targeting circulating exosomes, recently identified as promising cancer biomarkers. We introduce an innovative nano-photonic perfect absorber (NPA) operating in the terahertz (THz) range, offering a significant improvement over existing MWI-based approaches in terms of simplicity, sensitivity, and specificity. Unlike previous THz absorbers, the proposed NPA achieves an exceptionally wide operating bandwidth from 100 GHz to 50 THz with an absorption efficiency exceeding 97.5%, while featuring an ultra-compact nanoscale footprint (100 × 100 nm2, thickness 30 nm). The design integrates a silver (Ag) resonator and a nickel (Ni) ground plane on a silicon dioxide (SiO2) substrate, with meticulously tuned geometries to create multiple resonance modes, enabling continuous broadband absorption. Full-wave electromagnetic simulations validate the structure’s performance, including electric and magnetic field distributions, surface currents, and scattering parameters. Comparative analysis with state-of-the-art absorbers demonstrates the superior bandwidth, absorption stability, and angular robustness of our device. Furthermore, we demonstrate the NPA’s unique ability to act as a label-free biosensor for exosome detection, where cancerous exosomes consistently induce stronger electric field responses than normal exosomes due to their distinct molecular compositions. These results confirm the proposed NPA as a novel, highly effective platform for non-invasive, early-stage cancer diagnostics via MWI.